Kultur Masal Chidoridae - Hematang, Mezak; Lantu, Sartje (Universitas Sam Ratulangi, 2015)
The goal of mass culture of chydoridae is to find out the density of chydoridae that was cultured with yeast and rice bran. Chydoridae was cultured on 5 aquaria i.e 3 aquaria measuring 100 x 60 x cm (A, B and C) and 2 aquaria measuring 30 x 30 x 30 cm (D and E). Water quality parameters measured were temperature and pH. The result of chydoridae mass culture for 21 days reached the peak on 14th day with the result as follow : for aquarium A with the concentration of yeast and rice bran 0.05 g/500 mL is 31 individue/ml; aquarium B with the concentration of yeast and rice bran 0.03 g/500 mL is 13 individue/ml; aquarium C with the concentration of yeast and rice bran 0.03 g/500 mL is 5 individue/ml; aquarium D with the concentration of yeast and rice bran 0.005 g/500 mL and aquarium E with the concentration of yeast and rice bran 0.003 g/500 mL can not be detected. Counting the density of chydoridae on 21st day gave the result as follow : aquarium A as much as 4 individue/ml; aquarium B as much as 3 individue/ml; aquarium C as much as 2 individu/ml; aquarium D as much as 1 individue/ml and aquarium E as much as 2 individu/ml. During culturing, water quality such as temperature and pH were on the range that was not harmful the chydoridae life. Keywords: zooplankton, life food, chydoridae, fresh water, mass culture